2023
DOI: 10.3390/ijms24054668
|View full text |Cite
|
Sign up to set email alerts
|

MKP-1 Deficiency Exacerbates Skin Fibrosis in a Mouse Model of Scleroderma

Abstract: Scleroderma is a chronic fibrotic disease, where proinflammatory and profibrotic events precede collagen accumulation. MKP-1 [mitogen-activated protein kinase (MAPK) phosphatase-1] downregulates inflammatory MAPK pathways suppressing inflammation. MKP-1 also supports Th1 polarization, which could shift Th1/Th2 balance away from profibrotic Th2 profile prevalent in scleroderma. In the present study, we investigated the potential protective role of MKP-1 in scleroderma. We utilized bleomycin-induced dermal fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Fibroblasts can sense this protein and use it as a growth factor improving cell proliferation, survival, cell-matrix interactions and deposition of ECM during wound healing [ 54 56 ]. Recently, Scotece et al demonstrated that YKL-40 exhibited a sharp increase in skin in response to bleomycin treatment [ 57 ], and it has also been previously related to the progression of several inflammatory and fibrotic skin diseases, including systemic sclerosis, dermatitis and pyoderma gangrenosum [ 58 60 ]. Additionally, Ho et al (2014) demonstrated that a reduced population of primary dermal cells in culture (5–10% of total population) expresses YKL-40, but the expression was more widespread when the cells were treated with oncostatin M, a cytokine related to IL-6 family [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts can sense this protein and use it as a growth factor improving cell proliferation, survival, cell-matrix interactions and deposition of ECM during wound healing [ 54 56 ]. Recently, Scotece et al demonstrated that YKL-40 exhibited a sharp increase in skin in response to bleomycin treatment [ 57 ], and it has also been previously related to the progression of several inflammatory and fibrotic skin diseases, including systemic sclerosis, dermatitis and pyoderma gangrenosum [ 58 60 ]. Additionally, Ho et al (2014) demonstrated that a reduced population of primary dermal cells in culture (5–10% of total population) expresses YKL-40, but the expression was more widespread when the cells were treated with oncostatin M, a cytokine related to IL-6 family [ 61 ].…”
Section: Resultsmentioning
confidence: 99%